An analysis of determinants affecting the profitability of property and construction sectors in Malaysia - Neow Ean, Lee (2018)
This study analyses the factors influencing the profitability of 76 property companies and 28 construction companies listed in the Bursa Malaysia, from year 2009 to 2013. Profitability is proxied by return on equity (ROE) while the independent variables are quick ratio (QR) for liquidity, debt ratio (DR) and debt to equity ratio (DER) for leverage and finally, revenue (REVENUE) and total assets (TA) for firm size. Using panel data regression, the results indicated that size is the only variable that has significant relationship with profitability, with a positive relationship. The other variables are not significantly related to profitability. This shows that as far as the listed property and construction companies are concerned, size, as measured by total assets and revenue, is significant in determining the variation in the net profit. Based on this finding, it is recommended that other financial and non-financial variables including macroeonomics variables be included in the regression model for future studies on both sectors.